Deterrence now - Morgan, Patrick M., 1940- (Cambridge studies in international relations, 2003)
This authoritative book examines the place of deterrence after the Cold War. Patrick Morgan explores the state of deterrence theory and its continuing relevance under conditions of nuclear proliferation, collective security organisations, and a revolution in military affairs. This book makes a significant contribution to strategic studies and international relations.